A multi-agent based infrastructure to support virtual communities in elderly care. (14th October 2004) - Camarinha-Matos, Luis M.; Afsarmanesh, Hamideh
The growing numbers of the elderly population impose an urgent need to develop new approaches to care provision. The convergence of a number of technologies such as multi-agent systems, federated information management, safe communications, hypermedia interfaces, rich sensorial environments, increased intelligence of home appliances, and collaborative virtual environments, represents an important enabling factor for the design and development of virtual elderly support community environments. In this paper, a platform based on mobile agents combined with federated information management mechanisms is introduced as a flexible infrastructure on top of which specialised care services can be built.